The Problem of Female Subjectivity in the Novel “The Handwriting of Leonardo” by Dina Rubina - Afanasev, Anton; Breeva, Tatyana; Osmukhina, Olga (Journal of History Culture and Art Research, 2018)
The article is devoted to the consideration of the problem of female subjectivity, which is directly included in the process of conceptualizing the gender picture of the world. This problem occupies a central position in the novel by Dina Rubina’s "The Handwriting of Leonardo" (2008), while the main form of her artistic presentation is the heterotopy of the circus. The puzzle organization of this heterotopy allows you to focus attention on the circus culture as a way of life, as a kind of cosmos based on a transgressive act. D. Rubina, playing circus nomadism, turns the heterotopy of the circus into a space for the deployment of female subjectivity, an important role in this case is the fundamental refusal of the circus to "tell" and "reflect", its utmost demonstrativeness. Androgyny of the main heroine of the novel by Anna Nesterenko becomes an indirect evidence of the reduction of corporeality, focusing on the production of female subjectivity, the realization of which is associated with the motive of the mirror: the view "on oneself" reveals the result of looking "into oneself." One of the forms of representation of the mirror motif is the interaction of an objectified and personalized narrative, while the masculine-personalized narrative (with the epistolary of Senya and the monologized narrative of Volodya in conversation with the Interpol investigator Robert Kerler) fulfills in the novel the role of a peculiar mirror, allowing to realize the view "on oneself." The correlation of these two aspects becomes a reflection of the process of the formation of female subjectivity, the space for the unfoldment of which is the heterotopy of the circus de-centered in all its manifestations.